Optimalisasi Metode Qira'ati Untuk Meningkatkan Kelancaran Membaca Al-Qur’an di TPQ Roudhoh Samarinda - Soleha, Ainun; Tabina, Syafana Thalita; Hakim, Nuraini; Arianti, Ristia Dita; Azahra, Irma Zafiratunisa; Sari, Irni Maya; Nasrun, Moh. (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study aims to optimize the Qira'ati method to improve the fluency of reading the Qur'an at Taman Pendidikan Al-Qur'an (TPQ) Roudhoh, Samarinda Ilir. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 15 TPQ students with varying levels of Qur'an reading proficiency. The results showed that the intensive and systematic implementation of the Qira'ati method significantly improved reading fluency. In the first cycle, there was a 58% improvement in reading ability, which increased to 87% in the second cycle. This method proved effective due to its emphasis on mastering tajweed, repetitive practice, and individualized approaches. The study concludes that the Qira'ati method can serve as a primary strategy to enhance Qur'anic reading fluency in TPQ.